Alejo Venegas de Busto : un moraliste tolédan du xvie siècle face à l’hérésie - Marc Zuili (Les Cahiers de Framespa)
The purpose of this work is to analyse how a 16th-century Toledan moralist, Alejo Venegas de Busto (1498 or 1499?-1562) considered such a notion as heresy. This paper will be based on his writings, especially the Agonía del tránsito de la muerte (1537) – a work described by Marcel Bataillon as «a masterpiece of ascetic literature at the time of Charles V». After studying the question of Venegas’ orthodoxy – supposedly influenced by Erasmus –, this article will examine how this moralist presented and viewed heresy in his books and how he recommended opposing it. This work will lead us to address various topics such as the birth and spread of Lutheranism as well as the question of purity of blood (limpieza de sangre), so important in a Spain where Old Christians and Conversos used to live side by side.